2021
DOI: 10.1186/s12875-021-01400-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of providing a palliative approach to care in family practice: a chart review and perceptions of healthcare practitioners in Canada

Abstract: Background Most patients nearing the end of life can benefit from a palliative approach in primary care. We currently do not know how to measure a palliative approach in family practice. The objective of this study was to describe the provision of a palliative approach and evaluate clinicians’ perceptions of the results. Methods We conducted a descriptive study of deceased patients in an interprofessional team family practice. We integrated concep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Fourth, our objective was to evaluate whether there was a role for SICP in implementing ACP in primary care, and we did not undertake the study to increase the frequency of ACP conversations. However, a separate chart review of patients who died from January 2017 to December 2017 from the McMaster Family Health Team, found that 42% of decedents had a goals of care conversation, 32% discussed their illness understanding, 26% discussed patient values, beliefs and priorities going forward, and only 11% discussed prognosis [23]. A repeat chart review may be able to report on the potential impacts of SICP implementation on the frequency of ACP conversations.…”
Section: Limitationsmentioning
confidence: 99%
“…Fourth, our objective was to evaluate whether there was a role for SICP in implementing ACP in primary care, and we did not undertake the study to increase the frequency of ACP conversations. However, a separate chart review of patients who died from January 2017 to December 2017 from the McMaster Family Health Team, found that 42% of decedents had a goals of care conversation, 32% discussed their illness understanding, 26% discussed patient values, beliefs and priorities going forward, and only 11% discussed prognosis [23]. A repeat chart review may be able to report on the potential impacts of SICP implementation on the frequency of ACP conversations.…”
Section: Limitationsmentioning
confidence: 99%
“…4 In addressing these challenges, interdisciplinary medical teams worldwide are initiating, exploring, and providing palliative approaches to care. 5 7 …”
Section: Introductionmentioning
confidence: 99%
“…4 In addressing these challenges, interdisciplinary medical teams worldwide are initiating, exploring, and providing palliative approaches to care. [5][6][7] The palliative approach to care aims to improve quality of life and reduce suffering for people living with life-limiting conditions. 8 Typical provisions of the palliative approach include pain and symptom management, psychological, social,…”
mentioning
confidence: 99%